The Effect of Coating Thickness on Corrosion Resistance of Hydroxyapatite Coated Ti6Al4V and 316L SS Implants - Aksakal, B.; Gavgali, M.; Dikici, B. (Springer, 2010)
Hydroxyapatite (HAP) has been coated onto Ti6Al4V and 316L SS substrates by sol-gel method. The coating thicknesses for the analysis were about 40 and 72 mu m. Adhesion and corrosion tests have been conducted on uncoated and HAP-coated substrates. The coatings were characterized by XRD, SEM, and adhesion analysis. The corrosion resistance was examined in vitro by potentiodynamic polarization technique in Ringer's solution at room temperature. Electrochemical analysis indicated that the highest corrosion susceptibility was found on 72-mu m-coated 316L SS, and the 40-mu m HAP-coated Ti6Al4V showed the highest corrosion resistance. It was observed that the coating thickness was an effective parameter on both adhesion and corrosion resistance. It was shown that adhesion and corrosion resistance decreased with increasing coating thickness on both substrates.
Keywords: biomaterials; coatings; corrosion; sol-gel